Open-label dose-extending placebos for opioid use disorder: a protocol for a randomised controlled clinical trial with methadone treatment - Annabelle M Belcher; Thomas O Cole; Aaron D Greenblatt; Stephen W Hoag; David H Epstein; Michael Wagner; Amy S Billing; Ebonie Massey; Kristen R Hamilton; Zofia K Kozak; Christopher J Welsh; Eric Weintraub; et al. (BMJ Open)
Introduction More than 2 million individuals in the USA have an opioid use disorder (OUD). Methadone maintenance treatment is the gold standard of medication-based treatment for OUD, but high-dose methadone is associated with cardiotoxicity and respiratory complications, among other side effects. These adverse effects make enhancing the effectiveness of lower doses of methadone an attractive therapeutic goal. Long recognised for its capacity to enhance treatment outcomes for a wide range of neuropsychiatric disorders including pain, the placebo effect offers an as-yet untested avenue to such an enhancement. This approach is particularly compelling given that individuals with substance use disorder tend to have higher salience attribution and may thereby be more sensitive to placebo effects. Our study combines two promising clinical methodologies—conditioning/dose-extension and open-label placebo—to investigate whether placebo effects can increase the effective potency of methadone in treatment-seeking OUD patients.Methods and analysis A total of 120 newly enrolled treatment-seeking OUD patients will be randomly assigned to one of two different groups: either methadone plus daily placebo dose-extension (PDE; treatment group) or methadone/treatment as usual (control). Participants will meet with study team members five times over the course of 3 months of treatment with methadone (baseline, 2 weeks, and 1, 2 and 3 months postbaseline). Throughout this study time period, methadone dosages will be adjusted by an addiction clinician blind to patient assignment, per standard clinical methods. The primary outcome is methadone dose at 3 months. Secondary outcomes include self-report of drug use; 3-month urine toxicology screen results; and treatment retention. Exploratory outcomes include several environmental as well as personality factors associated with OUD and with propensity to demonstrate a placebo effect.Ethics and dissemination Human subjects oversight for this study is provided by the University of Maryland, Baltimore and University of Maryland, College Park Institutional Review Boards. Additionally, the study protocol is reviewed annually by an independent Data and Safety Monitoring Board. Study results will be disseminated via research conference presentations and peer-reviewed publications.Trial registration number NCT02941809.